Perlekatan Streptococcus mutans pada Aplikasi Fissure Sealant Berbahan Resin Dibandingkan dengan Ionomer Kaca Fuji VII (The Attachment of Streptococcus mutans for Fissure Sealant application Made of Resin Compare With Glass Ionomer Fuji VII) - Nazala Zetta Zettira; Niken Probosari; Pujiana Endah Lestari (Pustaka Kesehatan, 2017)
Background : Dental caries is the hard tissue disease. Caries is caused by multiple factors that is of them are morphology the surface of the tooth and bacteria Streptococcus mutans. The pit and fissure are primary habitats of S. mutans. Therefore, prevention of fissure sealants are needed. The materials of fissure sealant are composite resin and glass ionomer fuji VII. S. mutans can attach to foreign objects, one of them is material restoration. Objective : The purpose of this research is to know the difference of S. mutans attachment for fissure sealant application made of resin and glass ionomer fuji VII. Method : The experimental laboratory was post test only control design. The samples size from two group are 32 samples. The tool that used is spectofotometer with unit of measurement is colony forming unit a mL. Result and Conclusion : The average of S. mutans attachtment of composite resin and glass ionomer are 5,201 x 108 and 3,963 x 108. The attachtment was tested by independent sample T-tes there was differences of S. mutans attachment for fissure sealant application made of resin and glass ionomer fuji VII. Resin composite have a higher total number than ionomer fuji VII. Keywords: dental caries, fissure sealant, glass ionomer, resin, s. mutans,